Сутність та структура формування готовності тренерів з одноборств до згуртування спортивного колективу в умовах воєнного стану - Бутенко, К. В.; Butenko, K. V.; ORCID: https://orcid.org/0000-0002-4771-8883; Райтаровська, І. В.; Raitarovska, I. V.; Родигіна, В. П.; Rodyhina, V. P.; Мартиненко, О. М.; Martynenko, O. M.; ORCID: https://orcid.org/0000-0002-9380-1442; Богомол, Н. Д.; Bohomol, N. D. (Педагогіка формування творчої особистості у вищій і загальноосвітній школах. - 2022. - № 82. - С. 30-35, 2022)
Визначено сутнісні характеристики формування готовності тренерів, які спеціалізуються в одноборствах до змагальної діяльності (на прикладі тренерів з греко-римської боротьби): особистісне утворення, яке формується шляхом акцентованого та збалансованого педагогічного впливу на формування у тренерів, які спеціалізуються у спортивних видах боротьби (одноборствах) готовності до підтримання на високому рівні спортивних показників спортсменів та спортсменок, а також збірних команд (з олімпійських та неолімпійських видів одноборств) на міжнародній арені, особистому захисту України та підготовки патріотично налаштованих захисників та захисниць України в умовах воєнного стану (екстремальних умовах реалій сьогодення) та забезпечує поєднання ними знань про зміст та структуру системи багаторічної підготовки одноборців зі сформованими та усвідомленими ними в процесі розвитку потребами та потенційними можливостями.

ilitary threat According to the results of the analysis of scientific-methodical, special and reference literature, members of the research group found, that the question of determining the essential characteristics of the formation of the readiness of coaches who specialize in wrestling to unite national teams in the face of a military threat (hostilities in Ukraine) – insufficient number of scientific and methodical works is devoted, which requires further research and emphasizes the relevance and practical component of the chosen field of study. The main purpose of the study is to determine the nature and structure of the readiness of Greco-Roman wrestling coaches to unite the national team in conditions of military danger. During the research and analytical work the following research methods were used: axiomatic, idealization, historical and logical, convergence from the concrete, formalization, etc. As a result of theoretical research we have determined the essential characteristics of the formation of the readiness of coaches who specialize in martial arts for competitive activities (on the example of coaches in Greco-Roman wrestling) – personal education, which is formed by accentuated and balanced pedagogical influence on the formation of coaches who specialize in wrestling (martial arts) readiness to maintain a high level of sports performance of athletes, as well as national teams (from Olympic and non-Olympic types of martial arts) in the international arena, personal defense of Ukraine and training of patriotic defenders of Ukraine in conditions of military danger (extreme conditions of today’s realities) and provides them with a combination of knowledge about the content and structure of the system of long-term training of wrestlers with the needs and potential opportunities formed and realized by them in the process of development. In addition to the above, the members of the research group identified the dominant components: motivational, professionally applied, stress-resistant and functional – ensuring the readiness of coaches who specialize in martial arts (on the example of coaches in Greco-Roman wrestling) to professional activity in conditions of military danger (extreme conditions of today’s realities). Prospects for further research in the chosen field of scientific research include the development of pedagogical conditions for the consolidation of sports teams in martial law (on the example of highly qualified athletes who specialize in Greco-Roman wrestling).

Определены сущностные характеристики формирования готовности тренеров, специализирующихся в единоборствах к соревновательной деятельности (на примере тренеров по греко-римской борьбе): личностное образование, формируемое путем акцентированного и сбалансированного педагогического воздействия на формирование у тренеров, специализирующихся в спортивных видах борьбы (единоборствах) готовности к поддержанию на высоком уровне спортивных показателей спортсменов и спортсменок, а также сборных команд (с олимпийских и неолимпийских видов единоборств) на международной арене, личной защиты и подготовки патриотически настроенных защитников и защитниц Украины в условиях военного положения (экстремальных условиях реалий настоящего) и обеспечивает сочетание ими знаний о содержании и структуре системы многолетней подготовки единоборцев со сформированными и осознанными ими в процессе развития потребностями и потенциальными возможностями.
The essence and structure of the formation of the readiness of coaches who specialize in martial arts to unite the sports team in a military threat
Бутенко, К. В. Сутність та структура формування готовності тренерів з одноборств до згуртування спортивного колективу в умовах воєнного стану / К. В. Бутенко, І. В. Райтаровська, В. П. Родигіна та ін. // Педагогіка формування творчої особистості у вищій і загальноосвітній школах. - 2022. - № 82. - С. 30-35. - DOI: https://doi.org/10.32840/1992-5786.2022.82.4.
Keywords: Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Наукові публікації. Scientific publications. Научные публикации; Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; Україна. Ukraine. Украина; тренерська діяльність; coaching activity; тренерская деятельность; спортивний колектив; sports team; спортивный коллектив; згуртування; cohesion; сплочение; воєнний стан; martial law; военное положение; екстремальні умови; extreme conditions; экстремальные условия; готовність; readiness; готовность; одноборства; single combat; единоборства